2004
DOI: 10.1111/j.1083-4389.2004.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence ofHelicobacter pyloriAcquisition in Children of a Canadian First Nations Community and the Potential for Parent‐to‐Child Transmission

Abstract: The rate of childhood H. pylori acquisition was 16% over 1 year, and was not dependent on number of siblings infected. The finding of homologous H. pylori DNA in saliva and in soother water suggests the possibility of human to human transmission, particularly via an oral-oral route. Thus, there is the potential for further investigations in this population and other endemic communities that are directed at prevention of infection transmission via this modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…In addition, results of studies using PCR based on the primers studied here reporting the detection of H. pylori in environmental samples should be viewed with caution since even multiples of these primer sets produced a very high rate of false-positive results (i.e., 54% in saliva samples). Possibly, the accuracy and specificity could be improved by using magnetic beads or other techniques to separate the organism coupled with primers designed to detect H. pylori-specific proteins unrelated to urease (13,19,23) or possibly to have positive results with multiple potentially H. pylori-specific virulence genes (e.g., cagA or vacA) (40,46,54). The Human Microbiome Project should enrich the GenBank with many as-yet-uncultured human microbes such that searches should help eliminate primer pairs that cross-react with non-H. pylori bacteria and cause false-positive PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results of studies using PCR based on the primers studied here reporting the detection of H. pylori in environmental samples should be viewed with caution since even multiples of these primer sets produced a very high rate of false-positive results (i.e., 54% in saliva samples). Possibly, the accuracy and specificity could be improved by using magnetic beads or other techniques to separate the organism coupled with primers designed to detect H. pylori-specific proteins unrelated to urease (13,19,23) or possibly to have positive results with multiple potentially H. pylori-specific virulence genes (e.g., cagA or vacA) (40,46,54). The Human Microbiome Project should enrich the GenBank with many as-yet-uncultured human microbes such that searches should help eliminate primer pairs that cross-react with non-H. pylori bacteria and cause false-positive PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that H. pylori might be transmitted by saliva comes from a study by Megraud et al (13), who found a higher risk of H. pylori associated with the custom of the premastication of food when mothers feed their children in western Africa. Recently, Sinha et al (19) demonstrated H. pylori positive PCR in maternal saliva and in the water in which children's soothers (pacifiers) were stored suggesting a plausible route of mother-to-child oral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…As conclusive evidence for zoonotic transmission of H. pylori is not yet available (195), new infections are thought to occur as a consequence of direct human-to-human transmission, via either an oral-oral or fecaloral route or both. H. pylori has been detected in saliva, vomitus, gastric refluxate, and feces (10,177,178,298,361,492,569), but there is no conclusive evidence for predominant transmission via any of these products. This may be due to the fact that most research on transmission has focused on adults.…”
Section: Transmission and Sources Of Infectionmentioning
confidence: 99%